2001
DOI: 10.1038/sj.ejcn.1601206
|View full text |Cite
|
Sign up to set email alerts
|

Relation between body composition and age in healthy Japanese subjects

Abstract: Objective: To describe the relation between body composition and age measured by dual-energy X-ray absorptiometry (DXA) in healthy Japanese adults. Design: Cross-sectional study. Subjects and measurements: The subjects were 2411 healthy Japanese adults (males 625, females 1786, age 20 ± 79 y) who attended the Fukuoka Health Promotion Center, Fukuoka, Japan for health check-up. Body composition was determined by DXA (QDR-2000, Hologic) for the whole body and three anatomical regions of arms, legs and trunk. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 27 publications
2
48
1
6
Order By: Relevance
“…The subjects were not sampled randomly. However, we have already shown that the characteristics of our subjects are similar to those of the general Japanese population [17,19]. Finally, trunk FM measured by dual-energy X-ray absorptiometry cannot discriminate between subcutaneous and visceral FM.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The subjects were not sampled randomly. However, we have already shown that the characteristics of our subjects are similar to those of the general Japanese population [17,19]. Finally, trunk FM measured by dual-energy X-ray absorptiometry cannot discriminate between subcutaneous and visceral FM.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have demonstrated that larger HC decreases the risk of total mortality, cardiovascular mortality and morbidity, and cardiovascular risk factors independently of WC in Whites [8][9][10][11][12][13]. To date, no studies have examined such influence of HC on cardiovascular risk factors in large Asian populations, which show different characteristics of body composition and different relationship between body composition and cardiovascular risk factors compared with the Caucasian populations [14][15][16][17][18][19][20]. In addition, only a few studies, with relatively small populations, have investigated which component(s) of the body composition actually corresponds to the beneficial effects of HC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients under 18 years of age InBody J10 uses standard PBF for appropriate age classes (Heyward and Stolarczyk 1996;Lohman 1992;Tahara et al 2002;Fomon et al 1982). In Body J10 software, standard skeletal muscle mass (kg) is estimated with the assumption: 40-47% for boys and men and 40-42% for girls and women of standard body weight (Heymsfield et al 1990;Ito et al 2001).…”
Section: Bia Analysismentioning
confidence: 99%